Effect of Mindfulness Based Stress Reduction on Quality of Life (SF-36) and Spirometry Parameters in Chemically Pulmonary Injured Veterans - Zahra Arefnasab; Mostafa Ghanei; Ahmad Ali Noorbala; Ahmad Alipour; Farhang Babamahmoodi; Abdolreza Babamahmoodi; Maryam Salehi (Tehran University of Medical Sciences, 2013)
Background: Studies have shown that Mindfulness Based Stress Reduction (MBSR) has positive effect on physical and psychological dimensions of chronic illnesses. In this study for the first time we examine the effect of this new technique on quality of life and pulmonary function in chemically pulmonary injured veterans who have chronic pulmonary problem, psychological problems and low quality of life.Methods: Forty male pulmonary injured veterans were randomly replaced in two groups with 20 participants (MBSR and control Wait List (WL)). Then MBSR group received 8-weekly sessions intervention. We evaluate quality of life (used SF-36 questionnaire) and Spirometry parameters two times; before and after intervention in two group. We used "mixed factorial analyses of variance" test for analyzing data in each dependent variables. Then if we have significant interactional effect, we used "paired- sample t-test" for comparing before and after intervention data of each group, and "Independent-Sample t-test" for comparing after intervention data of two groups.Results: The MBSR compare to WL group improved SF-36 total score, (F (1, 38) =12.09, P=0.001), "Role limitations due to physical problems"(F(1,38)= 6.92, P=0.01), "Role limitations due to emotional problems"(F(1,38)= 7.75, P=0.008), "Social functioning"(F(1,38)= 9.89, P=0.003), "Mental health"(F(1,38)= 15.93, P=0), "Vitality"(F(1,38)= 40.03, P≤0.001), and "Pain"(F(1,38)= 27.60, P≤0.001). MBSR had no significant effect on "FEV1" (F (1, 38) = 0.03, P=0.85),"FVC" (F (1, 38) = 0.16, P=0.69) and "FEV1/FVC" (F (1, 38) = 2.21, P=0.14).Conclusion: MBSR can improve individual's quality of life but not lung function in chemically pulmonary injured veterans.